2019
DOI: 10.1111/mmi.14335
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of cell wall chitin via Ca2+–calcineurin‐mediated PKC signaling pathway maintains the viability of Candida albicans in the absence of β‐1,6‐glucan synthesis

Abstract: Summary β‐1,6‐glucan is an important cell wall component of Candida albicans. Deleted mutants of the two β‐1,6‐glucan synthase genes KRE6 and SKN1 are viable albeit with a range of defects including slow growth. It remains unclear whether β‐1,6‐glucan synthesis is not required under culture conditions or compensatory mechanisms exist in C. albicans. Here, we report that depleting β‐1,6‐glucan synthases leads to a significant increase in cell wall chitin levels through the posttranscriptional regulation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
(52 reference statements)
2
5
1
Order By: Relevance
“…Unlike Han et al (59), we found that very low nikkomycin concentrations further inhibit the growth of KRE6-depleted cells, as compensatory chitin synthesis is inhibited (Fig. 8B).…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…Unlike Han et al (59), we found that very low nikkomycin concentrations further inhibit the growth of KRE6-depleted cells, as compensatory chitin synthesis is inhibited (Fig. 8B).…”
Section: Discussioncontrasting
confidence: 89%
“…We found a higher chitin content in cells depleted of KRE6, as previously reported (59). This effect was completely or partially abrogated in cells lacking Pho84 (Fig.…”
Section: Loss Of Pho84 Prevented Compensatory Chitin Deposition In Cesupporting
confidence: 90%
See 2 more Smart Citations
“…Additionally, PHS‐1‐P as signaling molecules also can directly activate the conserved calcium responsive calcineurin‐Crz1 pathway in S. cerevisiae (Birchwood et al ., 2001). Considering the importance of the calcineurin‐Crz1 pathway in cell wall synthesis and maintenance (de Castro et al ., 2019; Han et al ., 2019b), it is possible that PHS‐1‐P regulates CWI by activating calcium signaling pathway. Taken together, sphingolipid can integrate multiple signaling pathways to regulate cell wall synthesis and maintenance (Dickson, 2010).…”
Section: Sphingolipids Are Required For Fungal Virulencementioning
confidence: 99%